Seasonal variation in the vertical distribution of zone over Oakshin Gangotri, Antarctica (MAUSAM, 1991)
Ozone soundings made from Dakshin Gangotri, Antarctica during 1987 are presented. The vertical distribution of ozone over Antarctica is characterised by a double peak profile, one around 200-150 hPa and the other around 50 hPa. During late winter-early spring the upper peak is considerably depleted. Tropospheric ozoe remains low and nearly constant throughout the year.